(untitled) (Research, Society and Development, 2022)
Gardnerella vaginalis is a bacterium that exists in the body of women who have an active sex life, and excessive growth can occur, producing a large number of bacteria at the site, and thus causing bacterial vaginosis. In this context, the objective of this study was to verify the predominance of Gardnerella vaginalis in women attended by the Basic Health Unit, Dr. Joaquim in Colmeia – Tocantins, Brazil. This study is a cross-sectional descriptive approach, whose target population was composed of 43 women attended at the Basic Health Unit, it was found that a high prevalence of Gardnerella Vaginalis colonizing the genital tract of women, being of great importance the orientation and adoption of adequate treatment by patients. Among the 43 samples, 62.64% had the pathology, another 37.36% are not correlated with the pathology, these data are related to age, sex life and numbers of partners, in addition, menopause is one of the conditions that influence in Gardnerella Vaginalis. Finally, it is very important to provide guidance and counseling for these women to have an adequate treatment for this disease.